New Dynamic Analysis and System Identification of Biodiesel Production Process from Palm Oil - Ahmmed S. Ibrehem; Hikmat S. Al-Salim (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2009)
In this study we present advanced mathematical model was used to capture the batch reactor characteristics of reacting compounds new parameters and new a prerequisite average slope analysis (PASA) method for the system dynamic behaviour under different operational conditions is a prerequisite to the good selection for these parameters. The model was applied to batch reactor for the production of bio-diesel from palm and kapok oils. Results of the model were compared with experimental data in terms of conversion of transesterification reaction for the production of bio-diesel under unsteady state. A good agreement was obtained between our model predictions and the experimental data. Both experimental and modeling results showed that the conversion of triglycerides to methyl ester was affected by the process conditions and by using PASA that could be achieved by making some deterministic tests either in real data plant or in the physical model that properly and adequately fits the actual process. The input-output relationships are studied using the open-loop dynamic response of the process, which can be determined from the process model by stepping different inputs and recording output responses. Starting from steady state conditions, each input is perturbed with certain magnitude that is enough to show the effect on the system dynamics. The transesterficition process with temperature of about 70 oC, and methanol ratio to the triglyceride of about 5 times its stoichiometry and the NAOH catalyst of wt 0.4%, appear to be acceptable process conditions. PASA shows methanol ratio to the triglyceride has big effect on the system. PASA method can be applied for different processes. © 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)